Total bakteri asam laktat dan Coliform pada ileum dan sekum ayam broiler yang diberi Spirulina platensis dengan lama pemberian berbeda - Muhammad Irfan Sulfani; Sugiharto Sugiharto; Turini Yudiarti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
This research was conducted to determine the amount of lactic acid bacteria and coliform inside the caecum and ileum of broilers. 240 days old chicks broiler (DOC) with 42.015 ± 0.219 g average body weight were used in this research as an experimental objects. The chicks broiler were treated with 0.04% antibiotics and 1% Spirulina plantensis as a prebiotic under different interval ingestion. This experiment was constructed under completely random design (CRD) with 4 treatments and 5 repetition. The treatment that was applied were T0 (Poultry feed + 0.04% Zinc bacitracin), T1 (Poultry feed + 1% throughout 7 days), T2 (Poultry feed + 1% throughout 21 days), and T4 (Poultry feed + 1% throughout 35 days). The parameter measurements conducted in the 32nd day with random sampling from each experiments. Total amount of lactic acid and coliform from each samples were observed and the variance was with 5% accuration. The result showed the total amout of Coliform in ileum was significantly different (P<0.05) in the other hand the total amount of Coliform and acid bacteria in caecum were not influenced (P<0.05). It can be inferred that the Spirulina platensis treatment for 3 weeks reduced the total amount of bacteria inside caecum and ileum.